Adopting a Global Virtual Team Approach to Enhance Performance of an International Nursing Research Collaboration. Issue 6 (November 2021) - Bish, Melanie; Stacey, Gemma; Shatto, Bobbi; Meyer, Geralyn
Abstract : Abstract: Global mobility, technological developments, and evolved organizational design have expanded the scope of workplace teams beyond traditional arrangements, giving rise to global virtual teams. As universities across the world encourage mobility, there are unprecedented opportunities to create discipline-specific international networks, increase cross-cultural understanding, and create rich interactions in research. Team structure, trust formation, and communication processes are known to positively influence global virtual team performance. They are discussed to illustrate the value of a structured model of work in an international research-focused collaboration of nursing academics from the United States, the United Kingdom, and Australia.